Dark academia : how universities die - Fleming, P. (Peter), 1972- (London : Pluto Press, 2021)
Bestselling author Peter Fleming uncovers the dark underbelly of the modern university to reveal cracks in the ivory tower.
Introduction: Infinite Hope ... But Not for Us -- 1. Dark Academia -- 2. La La Land -- 3. Welcome to the Edu-Factory -- 4. The Authoritarian Turn in Universities -- 5. You're Not a Spreadsheet With Hair -- 6. The Demise of Homo Academicus -- 7. High Impact ... -- 8. The Academic Star-Complex -- 9. Student Hellscapes -- 10. How Universities Die -- Conclusion: Are Some Lost Causes Truly Lost? -- Notes -- Index.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Universities and colleges; Neoliberalism; Universities and colleges -- Faculty -- Psychology; Universités.; Néo-libéralisme.; Universités -- Corps enseignant -- Psychologie; universities (institutions); colleges (institutions); BUSINESS & ECONOMICS -- General; Neoliberalism; Universities and colleges; Universities and colleges -- Faculty -- Psychology; Electronic book